2023
DOI: 10.3390/polym15102386
|View full text |Cite
|
Sign up to set email alerts
|

Poly(Lactic Acid) Composites with Lignin and Nanolignin Synthesized by In Situ Reactive Processing

Abstract: Poly(lactic acid) (PLA) composites with 0.5 wt% lignin or nanolignin were prepared with two different techniques: a) conventional melt-mixing and b) in situ Ring Opening Polymerization (ROP) by reactive processing. The ROP process was monitored by measuring the torque. The composites were synthesized rapidly using reactive processing that took under 20 min. When the catalyst amount was doubled, the reaction time was reduced to under 15 min. The dispersion, thermal transitions, mechanical properties, antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Two series of relatively new PLA–kraft lignin (kL) composites recently prepared by our groups 49 are studied here. Each series of polymer composites consists of neat linear PLA and two composites of PLA filled with 0.5 wt% micro-kL and nano-kL.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two series of relatively new PLA–kraft lignin (kL) composites recently prepared by our groups 49 are studied here. Each series of polymer composites consists of neat linear PLA and two composites of PLA filled with 0.5 wt% micro-kL and nano-kL.…”
Section: Methodsmentioning
confidence: 99%
“…42 Among others, the addition of lignin in polymers, including PLA, facilitates antioxidation and antibacterial performance. 46–49…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactive processing produced nanolignin-containing composites with superior crystallization, mechanical, and antioxidant properties. LNPs act as a macroinitiator in the ROP of lactide, resulting in PLA-grafted nanolignin particles, improved dispersion and the formation of interfacial covalent bonds facilitated by LNPs [201] Lignin-based nano-micelles using the "grafting-from" method pH-sensitive, biocompatible, suitable for oral drug delivery [202] Nanolignin/chitin nanofibrils and complexes loaded with active molecules, such as vitamin E, sodium ascorbyl phosphate, lutein, nicotinamide, and glycyrrhetinic acid Spray-drying method; nanostructured chitin; Functional agents in skin regeneration and antimicrobial, anti-inflammatory, and antioxidant activities; cytocompatibility in skin regeneration.…”
Section: Lignin Nanoparticles (Lnps)/starchmentioning
confidence: 99%
“…Various studies have explored the potential of PLA and lignin composites. Makri et al [8] demonstrated that reactive in situ processing can significantly enhance the properties of these composites, particularly when using nanolignin. Arjhan et al [9] found that the addition of lignin can reduce the tensile strength of PLA/lignin films, but also increase their elongation.…”
Section: Introductionmentioning
confidence: 99%